PENGARUH KEPEMILIKAN KELUARGA, PRAKTEK GOOD CORPORATE GOVERNANCE, PROFITABILITAS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN LISTING DI BURSA EFEK INDONESIA 2008-2012 - Sri Rezeki; Nur Azlina; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objectives of the research are to find out empirical evidence of the the effect of family Ownershipe, Corporate Governance Practices and profitability on Earnings Management of listing Companies. Ownership structure in this research using family ownershi, Corporate Governance is measured by three variables, size of Board of Commissioners, size of Board of management, the Audit Committee Composition and Profitabilitas. Data taken from the Indonesian Capital Market Directory (ICMD) and Financial Statements manufacturing company. The analysis method of this research using multiple regression. This research uses data from companies listed in Bursa Efek Indonesia (BEI) years from 2008 to 2012. Sample of this research are 80 sample companies. The results of this research indicate that variables which have significant influence on earnings managemen is an audit committee and profitability. Companies that establish an audit committee showed negative results, so the increasingly formation of audit committees can make earnings management practices decrease in that companies. Variable profitability show positive results, so if the company gives profitability to the management is high, then the practice of earning management will also be higher. Variable family ownership, size board of Commissioners, size of Board of management, does not have a significant influence on earnings management by firms.Keywords : earnings management, family ownership, good corporate governance, profitability.